Accounting Information Systems, Internal Control, and Financial Reporting Quality in Modern Enterprises in Bahrain - Ahmad al Haddad (Journal of Business Innovation and Accounting Research, 2025)
mechanisms, and financial reporting quality within modern enterprises operating in Bahrain. As a member of the Gulf Cooperation Council (GCC) region, Bahrain presents a unique context for examining these relationships given its adoption of International Financial Reporting Standards (IFRS) and its emerging economy characteristics. Employing a quantitative research methodology utilizing survey questionnaires distributed to financial professionals across Bahraini enterprises, this study examines how the implementation of AIS and the effectiveness of internal control systems influence the quality of financial reports. Drawing upon agency theory as the theoretical foundation, the research posits that robust AIS and effective internal controls reduce information asymmetry between management and stakeholders, thereby enhancing financial reporting quality. The findings reveal that both accounting information systems and internal control systems exert significant positive influences on financial reporting quality, with internal controls demonstrating a particularly strong relationship. The study contributes to the limited empirical literature on financial reporting quality in the Bahraini context and provides practical implications for enterprises seeking to enhance their financial reporting practices through technological and control-based interventions.